EREKTİL DİSFONKSİYONDA ENDOKRİN SEBEPLERİN GÖRÜLME SIKLIĞI - ALICI, Bülent; AKPINAR, Haluk; KANTAY, Kürşat Koray; ÖZKARA, Hamdi; AKKUŞ, Emre; HATTAT, Halim (Cerrahpaşa Medical Journal, 2019)
Background.-Little is known about the natural history of erectile dysfunction. Erectile dysfunction is clearly a symptom of many conditions and certain risk factors have been identified, some of which may be emanable to prevention strategies. Among these, hypogonadism in association with a number of endocrinologic conditions have been demonstrated as a risk factor. Design.-Over a period of 7 years, from 1991 to 1998, 2750 men who had referred to our sexual dysfunctions center for erectile dysfunction have been evaluated. Sexual hystory, physical examination, hormonal evaluation (prolactin, free testosterone), Doppler ultrasound, intracavernous pharmacotest and if indicated DICC and neurologic evaluation have been performed. Data were analyzed from the files of the patients. Patients with endocrinological causes without other etiology were included in the study group. The mean age of the patients were 39.2 (range 2375). The therapy given and results of the therapy were analyzed. Results.-Sexual history revealed 69/2750 (2.5 %) of the patients had primary impotence. 1100 (40.5%) patients were diabetic. Although diabetus mellitus is the most common endocrinologic cause of impotence, endocrine causes were detected in 190 patients (7%). In diabetic patients not only one factor could be determined as a cause of impotence. Cardiovascular disease was appearent in 495 patients (17.6%). Hormonal evaluation showed hyperprolactinemia in 19 of 190 (10%) patiens, hyperprolactinemia + androgen deficiency in 97 (50.8%), androgen deficiency in 74 (39.2%) patients. After the testosterone replacement therapy, 49 (70%) of the patients reported increase in penile rigidity and seminal volume and were satisfied with the therapy while 21 (30%) of the patients needed selfinjection pharmacotherapy. In patients with hyperprolactinemia, bromocriptine is used and only 16% of satisfactory results were obtained. Overall success rate was 37% with hormonal therapy. Conclusions.-Impotence is a major health concern. There are many determinants related to the risk factors and not only one factor could be determined as the etiological factor for erectile dysfunction. In patients with an etiology of endocrine causes, hormonal therapy is advisable but further other therapies may also be needed in case of unsatisfaction.